Infinite systems of stochastic differential equations and some lattice models on compact Riemannian manifolds - Daletskii, A. Yu.; Kondratiev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
Stochastic dynamics associated with Gibbs measures on an infinite product of compact Riemannian manifolds is constructed. The probabilistic representations for the corresponding Feller semigroups are obtained. The uniqueness of the dynamics is proved.